Dynamic Learning Organisations Supporting Knowledge Creation for Competitive and Integrated Product Design - Messnarz, R.; Spork, G.; Riel, A.; Tichkiewitch, S. (Cranfield University Press, 2009)
This paper shows that learning strategies and a structured approach to turn organisations into learning organisms have a major influence on the success of engineering programs in general, and on integrated design activities in particular. It points out the important relationship between dynamic learning organisations and the successful integrated development of complex mechatronic products using the topical and typical example of safety engineering in automotive development. It points out the key properties of learning organisations and reports about a way in which they have been successfully applied to the showcase example in close collaboration with a car manufacturing company.
Organised by: Cranfield University
Keywords: Learning Organisations; Competitive Design; Mechatronics; Certified Innovation Manager; EU Certificates